The Influence of the Ethnomathematical Learning Approach with Problem Based Learning Learning Model on Interests and Mathematics Learning Outcomes of Class VIII Students of MTs An-Nur Yapis Sorong City - marlinda indah eka budiarti; Zakiyah Anwar; Wilton Rahajaan (Universitas Pendidikan Muhammadiyah Sorong, 2022)
Abstact: This study aims to determine the effect of the ethnomathematics learning approach with a problem based learning model on the interest and learning outcomes of eighth grade students of MTs An-nur, Sorong City. This research is a pre-experimental research. The subjects of this study were class VIII students of MTs An-nur Yapis, Sorong City, in the 2021/2022 academic year. This research was conducted in 4 meetings. Data collection techniques are observation, questionnaires, tests, documentation and field notes. The data analysis technique in this research is quantitative. After the data is analyzed and the results of the T-Test test calculations are obtained, the tcount value is (-28,638) ttable (2,080) thus H0 is rejected and H1 is accepted, which means that there is an influence of the ethnomathematical learning approach with problem based learning learning models on interests and outcomes. students learn mathematics, class circle material at VIII MTs An-nur Yapis Sorong City. In addition, to see whether or not the problem based learning model has an effect on students' interest and learning outcomes in mathematics, it can be seen from the average results of the pretest and posttest with an average KKM value of 73. Student learning outcomes in the pretest 32.45 and posttest are 79, 04. Meanwhile, 11 students answered that they were very happy and 13 students answered that they were happy to use problem based learning because they could easily complete the teaching materials given. Thus, it can be concluded that learning by using an ethnomathematical learning approach with a Problem Based Learning model has been carried out well.